Electronic states and exchange interaction behaviors in crystal mixed system of (Ce1−XGdX)Ni (0≤ X≤0.8) through magnetic properties. (May 2017) - Yano, K.; Ohta, T.; Sato, K.
Abstract: Electronic states and exchange interactions in crystal mixed system between heavy fermion compound CeNi and ferrimagnet GdNi, (Ce1−X GdX )Ni compounds, were investigated in detail from macro-scopic magnetic properties in aid of molecular field analysis. In Gd-rich contents of x=0.8 and 0.5, the M - H curves at 2 K show normal-looking behaviors like those of ferro-magnets, however, closer quantitative analysis in M - H and M − 1/H curves reveal that the Ce magnetic moment decrease and could rotate continuously from anti-parallel to parallel to that of Gd and the measured total magnetization increases continuously after saturation without showing any discontinuities with the increase of magnetic field. No one can penetrate these behaviors without any information from micro-scopic measurements. On the other hand, in Gd-poor contents of x=0.2 and 0.15, the magnetic moments of Ce+Ni coupling anti-parallel to that of Gd decrease rapidly to one thirds in comparison with the value at Gd=0.8 and become about 0.2 μ B . The magnetization variations M ( T ) in Gd-poor contents show peculiar "linear" behaviors and the linear behaviors are found to stem from collapse-like decrease of RKKY interaction J Gd-Gd through molecular field analysis. In further decrease of Gd content, at x=0.03, the magnetic ordering of Gd is on set and the existence of Ni and Ce magnetic moments become uncertain. At x=0, that is, the CeNi shows a widely known behavior in M ( T ) and the M ( T ) is sensitive and nearly proportional to magnetic field H . Highlights: Crystal mixed system (Ce-Gd)Ni was investigated magnetically using molecular field analysis. In Gd-rich contents, spin-flip like behavior of Ce magnetic moment could be found in M - H curves. The Ce and Ni magnetic moments decreased with decrease of Gd content and became 1/3 at Gd=0.2. In Gd-poor contents, peculiar linear behaviors in M - T were observed and analyzed successfully. At Gd=0.03, 3 exchange interactions J ij and magnetic moments of Ce and Ni could disappear.